2007
DOI: 10.1590/s1516-35982007000600010
|View full text |Cite
|
Sign up to set email alerts
|

Taxa de prenhez de vacas Nelore lactantes tratadas com progesterona associada à remoção temporária de bezerros ou aplicação de gonadotrofina coriônica eqüina

Abstract: Avaliaram-se os efeitos da remoção temporária de bezerros (RTB) ou da aplicação de gonadotrofina coriônica eqüina (eCG) na taxa de prenhez (TP) de vacas Nelore lactantes tratadas com um dispositivo intravaginal liberador de progesterona (DILP). No experimento 1, 83 vacas Nelore e 102 mestiças (Nelore × Red Angus) foram distribuídas em três grupos. Em dia aleatório do ciclo estral (D0), os animais do grupo 1 foram tratados com benzoato de estradiol (BE; 2,5 mg, IM, Estrogin®) e um DILP (1 g de progesterona, DIB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 18 publications
1
6
0
5
Order By: Relevance
“…Percentage for G2 was similar to that described for zebu cattle by , with pregnancy rates between 45% and 67% and by Ereno et al (2007) between 50% and 54%. It was also similar to crossbreed cows in Moraes et al (2007) Progestagen (IPRD) associated with estradiol benzoate (EB) was employed in the two experimental groups, following reports by Moreira et al (2000) who described variations in the tested hormonal protocols.…”
Section: Resultssupporting
confidence: 81%
“…Percentage for G2 was similar to that described for zebu cattle by , with pregnancy rates between 45% and 67% and by Ereno et al (2007) between 50% and 54%. It was also similar to crossbreed cows in Moraes et al (2007) Progestagen (IPRD) associated with estradiol benzoate (EB) was employed in the two experimental groups, following reports by Moreira et al (2000) who described variations in the tested hormonal protocols.…”
Section: Resultssupporting
confidence: 81%
“…Suggested strategies for the recovery and accumulation of organic reserves of multiparous and/or primiparous cows include the designation of quality pastures and the temporary removal of calves along with hormone treatment with a progesterone-releasing intravaginal device (Ereno et al, 2007), allowing cows to reach appropriate body conditions to return to the mating season. Vaz, Lobato & Restle (2010) reported that the early weaning of calves at 76 days of age allowed a greater weight recovery post-weaning and longer reproductive periods in beef cows, thereby improving their body condition and increasing the rate of pregnancy compared to cows that continued nursing until 148 days of age.…”
Section: Resultsmentioning
confidence: 99%
“…Sá Filho e Vasconcelos (2010) obtiveram taxa de concepção de 50,6% ao usarem 316 matrizes no pós-parto de até 110 dias, após uma única IATF. Porcentagem semelhante à descrita por Ereno et al (2007), ao usarem 87 vacas Nelore com até 90 dias pós-parto. Portanto, o fornecimento de progestágeno promove aumento considerável na taxa de concepção em uma única IATF.…”
Section: Materiais E Métodosunclassified